Brief Report: Differential Effects of Tenofovir, Abacavir, Emtricitabine, and Darunavir on Telomerase Activity In Vitro. (1st January 2017) - Stella-Ascariz, Natalia; Montejano, Rocío; Pintado-Berninches, Laura; Monge, Susana; Bernardino, José I.; Pérez-Valero, Ignacio; Montes, María L.; Mingorance, Jesús; Perona, Rosario; Arribas, José R.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: In vitro, tenofovir and abacavir induced a significant dose-dependent inhibition of telomerase activity at therapeutic concentrations in peripheral blood mononuclear cells of healthy subjects. Median inhibition of telomerase activity by tenofovir at 0.5 and 1 μM was 29% [Interquartile range (IQR) 29%–34%, P = 0.042] and 28% (IQR 28%–41%, P = 0.042), respectively. Abacavir inhibition was 12% (IQR 9%–13%, P = 0.043) at 3 μM and 14% (IQR 10%–29%, P = 0.043) at 10 μM. Tenofovir and abacavir did not change human telomerase reverse transcriptase (hTERT) levels or mRNA levels of other telomerase complex genes. Exposure to emtricitabine or darunavir did not affect telomerase activity, hTERT protein levels, or mRNA levels of telomerase/shelterin genes.